The Influence of Competence and Training on Employee Performance at the Transportation Agency of Musi Banyuasin Regency: The Mediating Role of Job Satisfaction - Agung Setyabudi; Zunaidah; Muhammad Ichsan Hadjri; Wita Farla; Yomeini Margareth (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study examines the effects of competence and training on employee performance, with job satisfaction serving as a mediating variable. The research was conducted at the Transportation Agency of Musi Banyuasin Regency using a quantitative approach with an explanatory research design. A census sampling technique was employed, involving all 115 employees as research respondents. Data were collected using a structured Likert-scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The findings indicate that both competence and training have positive and significant effects on employee performance and job satisfaction. In addition, job satisfaction exerts a positive and significant effect on employee performance. The mediation analysis further demonstrates that job satisfaction significantly mediates the relationships between competence and employee performance as well as between training and employee performance. These findings suggest that improving employee competence and implementing effective training programs not only enhance employees' capabilities but also strengthen job satisfaction, which subsequently leads to improved employee performance. This study highlights the importance of integrating competence development, training initiatives, and job satisfaction enhancement strategies to achieve sustainable improvements in organizational performance